Препродакшен в анімації. Етапи підготовки та оптимізація робочого процесу - Товма, С. С.; Вовк, О. В. (ХНУРЕ, 2025)
Pre-production is a crucial phase in animation, shaping its quality and efficiency. It includes concept development, scriptwriting, storyboarding, and design of characters and environments. The storyboard outlines composition, movement, and transitions. Design work establishes visual identity and stylistic consistency. Technical planning sets parameters like resolution and frame rate. Animatics offer a preview to adjust before full production. Specialized software optimizes workflow and collaboration. Effective pre-production minimizes risks and ensures project success.
Keywords: анімація; оптимізація робочого процесу